2021
DOI: 10.1016/j.envres.2021.110795
|View full text |Cite
|
Sign up to set email alerts
|

Per- and polyfluoroalkyl substances in serum and associations with food consumption and use of personal care products in the Norwegian biomonitoring study from the EU project EuroMix

Abstract: Background: Human exposure to chemicals through the oral, dermal, or inhalation routes is significant. To assess this exposure, a human biomonitoring study was conducted in Norway to examine the plausibility of source-todose calculations for chemical mixtures. Per-and polyfluoroalkyl substances (PFASs) are man-made compounds used for their surfactant properties, and several are persistent and bioaccumulative. Some PFASs are toxic and are regarded as endocrine disruptors and have been shown to suppress immune f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…The serum concentrations of PFOPA (median: 0.69 ng/mL) in pregnant women were similar to those reported for occupationally exposed waste recycling workers (0.76 ng/mL) in that study and higher serum concentrations of PFOPA were found in waste sorters (0.61 ng/mL) and stevedores (0.77 ng/mL) than in managers (0.20 ng/mL) in the waste recycling factory, suggesting that sorters and stevedores may be directly exposed to PFOPA . Furthermore, our serum PFOPA concentrations were higher than those found in the general population (<0.03 ng/mL) in Norway. , These results suggest that e-waste dismantling activities also contributed to exposure to PFOPA.…”
Section: Results and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The serum concentrations of PFOPA (median: 0.69 ng/mL) in pregnant women were similar to those reported for occupationally exposed waste recycling workers (0.76 ng/mL) in that study and higher serum concentrations of PFOPA were found in waste sorters (0.61 ng/mL) and stevedores (0.77 ng/mL) than in managers (0.20 ng/mL) in the waste recycling factory, suggesting that sorters and stevedores may be directly exposed to PFOPA . Furthermore, our serum PFOPA concentrations were higher than those found in the general population (<0.03 ng/mL) in Norway. , These results suggest that e-waste dismantling activities also contributed to exposure to PFOPA.…”
Section: Results and Discussionsupporting
confidence: 88%
“…Information with regard to the occurrence of PFOPA in humans is very limited. , This is the first study to report the occurrence of PFOPA in pregnant women. The serum concentrations of PFOPA (median: 0.69 ng/mL) in pregnant women were similar to those reported for occupationally exposed waste recycling workers (0.76 ng/mL) in that study and higher serum concentrations of PFOPA were found in waste sorters (0.61 ng/mL) and stevedores (0.77 ng/mL) than in managers (0.20 ng/mL) in the waste recycling factory, suggesting that sorters and stevedores may be directly exposed to PFOPA .…”
Section: Results and Discussionmentioning
confidence: 99%
“… 54 , 55 Another approach to estimate exposure is human biomonitoring, through analysis of CAG-specific contaminants and their metabolites in human biomaterial, particularly urine and blood. 56 , 57 , 58 Such information, combined with analysis of potential sources of the measured contaminants, can help to build and refine physiologically based pharmacokinetic models for estimating internal human exposure. 59 As explained above, exposure data of multiple contaminants can be converted into a mixture dose using RPFs, expressed as a total dose of a reference compound, where all (also low) doses of individual compounds should be included in the calculation.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have reported positive associations between use of cosmetics and personal care products and internal levels of PFAS. Personal care product use has been associated with serum levels of perfluorononanoic acid (PFNA), PFOA, perfluorotridecanoic acid (PFTrDA), and perfluorooctane sulfonamide (PFOSA) . Applying cosmetics and personal care products has been identified as a potential source of perfluoroheptanoic acid (PFHpA) and PFOS in breast milk, respectively .…”
Section: Introductionmentioning
confidence: 99%